REVEALING THE KEY TO FINANCIAL STABILITY DURING THE COVID-19 CRISIS - Eogenie Lakilaki; Annisa Syaqbania; Rizki Amelia (Journal of Applied Accounting and Taxation, 2024)
The Covid-19 pandemic has caused a significant shock to the financial sector, affecting the performance and stability of financial institutions. This study aims to analyze the effect of the Loan to Deposit Ratio (LDR), capital adequacy, and credit risk on financial stability during the Covid-19 pandemic. The sample 18 banking sector companies listed on the Indonesia Stock Exchange during the 2020-2022 period. This research method uses relevant and reliable data from the banking sector companies listed on the Indonesia Stock Exchange during the Covid-19 pandemic period. Data analysis was performed using statistical regression techniques to identify the relationship between the variables studied. The results of this study are expected to provide further understanding of how changes in the Loan to Deposit Ratio, capital adequacy, and credit risk impact financial stability during the Covid-19 pandemic. The results of this study prove that the loan to deposit ratio and capital adequacy has a positive effect on the on the financial stability. While the credit risk have a negative effect on the financial stability. The implications of this research can be a guide for financial authorities and related institutions in making policies to maintain financial stability in the midst of a pandemic crisis. Keywords: Capital Adequacy Ratio, Financial Stability, Loan Deposit to Ratio, Non-Performing Loans